1982
DOI: 10.1042/bj2080419
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid oxidation by liver and muscle preparations of exhaustively exercised rats

Abstract: The influence of exhaustive exercise on the capacity of liver and muscle of rats to oxidize fatty acids was investigated in vitro. The rate of oxidation of fatty acids by liver preparations was significantly elevated as a result of exhaustion. Concurrently, the concentrations of beta-hydroxybutyrate were elevated in the plasma of the exhausted rats, suggesting that oxidation of fatty acids was also elevated in vivo. These findings are analogous to the findings of increased oxidation of fatty acids that results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 25 publications
(23 reference statements)
2
12
0
Order By: Relevance
“…Effects may be reversible in ways that prevent later detection. Animal studies have been made with rats [2,11,12,30] and horses [7,17], and they indicate impaired function of isolated mitochondria, in agreement with the morphological observations mentioned above. On the other hand, studies of human isolated mitochondria showed no impairment upon exhaustion [32,52,53,54].…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Effects may be reversible in ways that prevent later detection. Animal studies have been made with rats [2,11,12,30] and horses [7,17], and they indicate impaired function of isolated mitochondria, in agreement with the morphological observations mentioned above. On the other hand, studies of human isolated mitochondria showed no impairment upon exhaustion [32,52,53,54].…”
Section: Introductionsupporting
confidence: 77%
“…As much as 55% inhibition was detected after five track runs. Studies of trained rats showed that the specific respiratory activities of isolated mitochondria with pyruvate + malate [12] and palmitoyl-carnitine + malate [2] were lowered after exhaustion. The observation of decreased succinate respiration [12] was apparently not confirmed later [11].…”
Section: Discussionmentioning
confidence: 99%
“…As oxidative stress is commonly reported following eccentric exercise (Nikolaidis et al 2008), we suggest that it could be involved in reducing state 3 in the current study. Depressed mitochondrial RCR has been reported previously postexercise (Barakat et al 1982;Davies et al 1982;Fernstrom et al 2007) although this is not a consistent Wnding (Madsen et al 1996a) and has only been observed immediately post-exercise. The hypothesis that RCR would be depressed 48 h post-exercise was based on the substantial increases in MCC observed at this time point (Duan et al 1990).…”
Section: Discussionmentioning
confidence: 81%
“…Thus, although there is rodent data indicating that hepatic -oxidation may increase acutely with exercise (Barakat et al 1982) and direct human evidence that lipoprotein-derived fatty acids are oxidized by skeletal muscle during exercise (Kiens 1993) and that VLDL clearance may increase (Malkova et al 2000), the current Wndings may suggest that the level of lipoprotein export and oxidation is insuYcient to induce a reduction in HTGC during exercise or in the post-exercise period. Namely, unlike IMTG, the exercise-induced increase in adipose lipolysis (as suggested by our FFA, glycerol and TG data) and subsequent inXux of FFA into the liver may outweigh the capacity of the liver to oxidize and/or export fatty acids resulting in their accumulation in the triglyceride pool.…”
Section: Discussionmentioning
confidence: 84%